Constructing Institutional Measures: Indicators of Political and Property Rights in Mozambique, 1900–2005. Issue 4 (21st November 2012) - Luiz, John Manuel; Pereira, Luis Brites; Oliveira, Guilherme
Abstract : In this article, we focus on the role of political and economic institutions in Mozambique's development. We produce a set of institutional indicators for Mozambique for the period 1900–2005. The first index tracks political freedoms and is unique in its duration and complexity. The second index is a measure of property rights for Mozambique, and such a measure has not existed previously and certainly not for this length of time. The construction of these indices is a painstaking process through historical records but it provides us with a richness of institutional data previously not available. The new institutional indices will allow us to explore the role of the institutional environment in determining economic growth and development in Mozambique over time.